A Walk in the Night with Zhuangzi : Musings on an Ancient Chinese Manuscript. - Huang, Kuan-yun (State University of New York Press, 2023)
A complete translation and analysis of "All Things Flow into Form" (Fan wu liu xing), a recently discovered manuscript from the Warring States period (481-221 BCE).
Keywords: Fan wu liu xing.; Philosophy, Chinese -- To 221 B.C.; Philosophie chinoise -- Jusqu'à 221 av. J.-C.; Philosophy, Chinese.; To 221 B.C.